2010
DOI: 10.1542/peds.2009-0990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music by Mozart on Energy Expenditure in Growing Preterm Infants

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Music has been shown to reduce stress, decrease heart rate and salivary cortisol, and increase oxygen saturation, nonnutritive sucking rate, and even weight gain in preterm infants. WHAT THIS STUDY ADDS:Exposure to Mozart music significantly lowers REE in healthy preterm infants. abstract OBJECTIVE: The rate of weight gain in preterm infants who are exposed to music seems to improve. A potential mechanism could be increased metabolic efficiency; therefore, we conducted this study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
86
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 12 publications
(19 reference statements)
4
86
0
9
Order By: Relevance
“…Lubetzky et al (12) assessed 20 healthy PTNB in order to test the hypothesis that the "Mozart effect" reduces the resting energy in growing patients, and observed that those submitted to sessions of 30 minutes of music therapy twice a day presented reduction of energy expenditure compared to the group that was not exposed to music therapy. Schlez et al (19) , in turn, compared the use of the "Kangaroo Mother" Method (KMM) alone and in combination with music therapy, recommending the use of music therapy as an adjuvant for the preterm infants and their mothers while in the NICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lubetzky et al (12) assessed 20 healthy PTNB in order to test the hypothesis that the "Mozart effect" reduces the resting energy in growing patients, and observed that those submitted to sessions of 30 minutes of music therapy twice a day presented reduction of energy expenditure compared to the group that was not exposed to music therapy. Schlez et al (19) , in turn, compared the use of the "Kangaroo Mother" Method (KMM) alone and in combination with music therapy, recommending the use of music therapy as an adjuvant for the preterm infants and their mothers while in the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of songs was based on studies that showed the "Mozart effect", term used to refer to the powers of transformation of music in health, education, and well-being, representing, in general, the use of music to reduce stress, pain, depression, and anxiety; induce relaxation and sleep; restore the body; and improve memory and alertness (12) . The choice of music was based on previous studies, which have shown that relaxing music (soft classical) is composed of low amplitudes, simple rhythm, and frequency (time) of approximately 60 to 70 beats per minute (7) .…”
Section: Methodsmentioning
confidence: 99%
“…6 Endurance of the traumatic effects of premature birth and subsequent NICU admission 7,8 expends vital energy for the premature infant and can complicate or impair development. [9][10][11] An infant' s capacity to recognize his or her mother' s voice indicates that attention to this function may be valuable if integrated with NICU care practices. 12 Vocal familiarity within the infant' s sound environment may provide an essential domain of consistency, security, and comfort that even the most modern NICUs cannot replicate.…”
mentioning
confidence: 99%
“…13 Although there is good evidence that the mother' s voice and her singing of lullabies have positive outcomes, some studies have implemented recordings of Mozart' s music, 14,15 and 1 study hypothesized a "Mozart effect" as an outcome. 11 Several studies have implemented therapist-selected music 15,16 and other applications including children' s singing, 18 male or female singing, 19 and the use of specific music genres common to the region of study 1,20 with varying results. Several studies designed by a physician/musician implemented recorded womb sounds and interwoven music with positive results.…”
mentioning
confidence: 99%
“…19,20 In the small amount of literature about the benefits of EE for infants at risk for brain injury, we know that premature infants demonstrate neurobehavioral benefits from sensory-specific EE activities, such as massage 21 and music. 22 Developmental care interventions for premature infants have been shown to deliver modest short-term gains, but with some trials showing no benefit at all. 23 Some programs, such as The Newborn Individualized Developmental Care and Assessment Program, a sensory-specific EE and cue-based intervention for high-risk infants, has been shown to positively influence brain function and motor development.…”
mentioning
confidence: 99%